Psychotherapy for immigrant youth - Patel, Sita; Reicherter, Daryn (Springer, 2016)
This book provides an in-depth, practical, and cutting-edge summary of psychotherapy for immigrant children and adolescents. This text integrates practical therapeutic methods with current empirical knowledge on the unique life stressors and mental health concerns of immigrant youth, proving essential for all who seek to address the psychological needs of this vulnerable and under-served population. Specific chapters are devoted to trauma, refugees and forced displacement, cognitive-behavioral therapy, psychopharmacological issues, school-based treatment, family. Each chapter includes specific cultural concerns and treatment techniques for immigrant groups from various regions of the world. In-depth case examples illustrate case formulation, how and when to use specific techniques, challenges faced in the treatment of immigrant youth, and responses to common obstacles. With detailed theory and practice guidelines, Psychotherapy for Immigrant Youthis a vital resource for psychologists, psychiatrists, social workers, and other practitioners.